COVID-19 pandemic in Indonesia: Situation and challenges of rehabilitation medicine in Indonesia - Boya Nugraha; Luh Karunia Wahyuni; Hening Laswati; Peni Kusumastuti; Angela BM Tulaar; Christoph Gutenbrunner (Interna Publishing, 2020)
Abstrak COVID-19 telah menjadi pandemik di Indonesia sejak ditemukannya kasus pertama pada tanggal 2 Maret 2020 di Depok. Peningkatan kasus perhari semakin tinggi sejak akhir Agustus 2020 yang mencapai lebih dari 2000 kasus per hari. Sistem kesehatan di Indonesia perlu ditingkatkan dalam hal kapasitas, termasuk rehabilitasi medik yang harus dilibatkan dari fase akut hingga jangka panjang dalam penanganan pasien COVID-19. Rehabilitasi medik juga diperlukan untuk pasien lain yang bukan COVID-19. Pentingnya keterlibatan, pelayanan rehabilitasi medik dan implementasinya dimasa pandemic COVID-19 memerlukan strategi tersendiri yang harus dilakukan baik oleh pekerja kesehatannya, rumah sakit dan kebijakan pemerintah. Hal ini diperlukan untuk percepatan peningkatan kesehatan pasien, percepatan pemulangan dan menghindari readmisi pasien, dan juga pengoptimalan program kembali bekerja untuk pasien yang sembuh dari COVID-19. Abstract COVID-19 has become a pandemic in Indonesia since the first cases have been positively diagnosed on 2 March 2020 in Depok. The cases have been increased gradually since the end of August 2020 that has reached 1000 cases per day. The health system in Indonesia needs to be improved in terms of capacity, including rehabilitation medicine that should be involved in all health phases (from acute to long-term) in managing patients with COVID-19. Rehabilitation is also still needed for other non-COVID-19 patients. The importance of involvement and implementation of rehabilitation services during the COVID-19 pandemic will need special strategies that should be done by rehabilitation professionals, hospitals, and government. These are necessary to accelerate the improvement of patients' health, discharge, and avoid re-admission, as well as optimize return-to-work for patients who are recovered from COVID-19.